Pengaruh Human Relation (Hubungan antar Manusia), Semangat Kerja dan Budaya Kerja terhadap Kinerja Karyawan Diva Kraksaan Kabupaten Probolinggo - Hoirotul Wahyuningtyas; Titik Musriati; Yekti Rahajeng (JUMAD : Journal Management, Accounting, & Digital Business, 2024)
The purpose of this study was to determine the effect of human relations, work spirit and work culture variables on employee performance partially at diva swalayan kraksaan, probolinggo regency. This type of research uses quantitative research methods with an associative approach. The population was 150 permanent employees of Diva Swalayan Kraksaan Probolinggo Regency with a sample of 109 respondents. Determination of the sample using the Slovin formula. The sampling technique in this study used probability sampling with simple random sampling. Data analysis used, namely, validity test, reliability test, classical assumption test, multiple linear regression analysis, coefficient of determination (R2), hypothesis testing (t test). The results show that human relations, work spirit, work culture have a positive and significant effect on employee performance.